Rent control and housing justice - Slater,Tom (2020)
In this article I explore the question of rent control: one of the most despised yet misunderstood policies across a variety of disciplines and professions concerned with urban and housing issues. The hegemonic view is that rent controls - in any form, in any context - will eventually hurt those on whose behalf they are supposedly introduced (people struggling to find somewhere affordable to live). I use the concept of agnotology - the study of the intentional production of ignorance - to demonstrate that this view is riddled with vested interests and grounded in deep contempt for state regulation and in veneration of the supposed efficiency of the free market. I expose and dissect three of the prevalent myths of rent control: (1) that it negatively affects the quality of rented properties; (2) that it negatively affects the supply of housing; and (3) that it leads to inefficiencies in housing markets. I take a close look at different kinds of rent control and, more broadly, at what leads to high housing costs, and by doing so I shift the analytical and political focus towards the urgent question of housing justice.